Effect of chlorpyrifos on some biochemical changes in Cyprinus carpio: the protective effect of ellagic acid - Mise Yonar, Serpil; Yonar, Muhammet Enis; Ural, Mevlut Sener; Pala, Aysegul (Taylor & Francis Ltd, 2022)
In this study, ameliorative effects of ellagic acid (EA) on oxidative stress induced by chlorpyrifos (CPF) in carp, Cyprinus carpio, were investigated. Fish were divided into six groups: C (no treatment), EA (100 mg kg fish(-1)), CPF-1 (0.040 mg L-1), CPF-2 (0.080 mg L-1), CPF-1 + EA, and CPF-2 + EA. CPF and EA were applied simultaneously for 14 days and, at the end of the study, liver, kidney, and gill samples were collected from fish. On the taken tissue samples, malondialdehyde (MDA) level and some antioxidant enzyme (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione-S-transferase (GST)) activities were evaluated. The results demonstrated statistically significant increases in the MDA levels of the CPF-1 and CPF-2 groups. On the other hand, the MDA levels were significantly decreased by EA administration. Also, CPF exposure caused statistically significant increases in the SOD and GST activities and statistically significant decreases in the CAT and GPx activities. However, treatment with EA reversed negative alterations in the SOD, CAT, GPx, and GST activities. Therefore, the results of this study results showed that simultaneous treatment with EA alleviates CPF-induced oxidative stress in fish.
Keywords: Antioxidant enzyme; carp; chlorpyrifos; ellagic acid; oxidative stress; pesticide